Formation of n- and p-type regions in individual Si/SiO2 core/shell nanowires by ion beam doping. (25th September 2018) - Berencén, Y; Prucnal, S; Möller, W; Hübner, R; Rebohle, L; Schönherr, T; Khan, M Bilal; Wang, M; Glaser, M; Georgiev, Y M; Erbe, A; Lugstein, A; et al.
Abstract: A method for cross-sectional doping of individual Si/SiO2 core/shell nanowires (NWs) is presented. P and B atoms are laterally implanted at different depths in the Si core. The healing of the implantation-related damage together with the electrical activation of the dopants takes place via solid phase epitaxy driven by millisecond-range flash lamp annealing. Electrical measurements through a bevel formed along the NW enabled us to demonstrate the concurrent formation of n- and p-type regions in individual Si/SiO2 core/shell NWs. These results might pave the way for ion beam doping of nanostructured semiconductors produced by using either top-down or bottom-up approaches.